La décision d’implication internationale au sein de l’entreprise privée - Béliveau, Donald; Billardon, Jean-François (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
With the numerous improvements in the field of communication and the recent trends in high technology, changes in international management approach have occured and among the consequences can be found a uch higher degree of international economic dependance between the countries. The governments, in general, have put a lot of emphasis on programs that can help manufacturing businesses get involved in international development since they represent the prime motor to economic development. This article is based on a study whose main objective was to learn about the decision process of businessmen when itcomes to internationalization and to identify some of their perceptions as well as their degree of satisfaction in regard to a certain number of Canadian and Quebec government programs. The results are based on 480 usable returned questionnaires. The conclusions are to the effect that for the businessmen interested in international development, the main motivations are linked to international opportunities, unexploited production capacity and financial help through government programs. There is also indication that the type of government help needed will differ with the level of implications of the business in the international field.